Experimental study on heat transfer characteristics of a ⊥-shaped oscillating heat pipe used in the battery thermal management system - Hongkun, Lu; Noor, M. M.; Ning, Shuigen; K., Kadirgama; Badruddin, Irfan Anjum; Kamangar, S. (Semarak Ilmu Publishing, 2024)
This paper introduces a ⊥-shaped oscillating heat pipe (OHP) with the purpose of improving the volumetric utilization of the battery thermal management system (BTMS) for electric vehicles. Distinguished from standard OHP structures, the evaporator and condenser sections of the ⊥-shaped OHP are oriented vertically in spatial arrangement. Experimental investigations were conducted on two types of ⊥-shaped OHPs and a standard OHP, employing filling ratios from 19.6% to 39.1%, working fluid mixtures of acetone with methanol, ethanol, and water, and thermal loads from 10 to 100W. The results indicate that all the OHPs with an acetone filling ratio of 26.1% exhibit minimum thermal resistance at 30W. When employing mixed working fluids, the acetone-ethanol and acetone-methanol combinations display the least and most temperature fluctuations, respectively. The OHP with mixed working fluids achieves no more improved thermal performance than the use of acetone. As the heating power increases, the operational stability of the ⊥-type OHP improves, however, the trend is opposite for the R-⊥-type OHP. In comparison to the standard OHP, the ⊥-type OHP demonstrates stronger oscillation stability at 100W and achieves a 3.3°C lower maximum temperature on the heat collector plate.